Biofilm in periodontitis - Widowati, Witjaksono (2015)
Chronic Periodontitis may be defined as a mixed infection affecting individual or multiple sites within the oral cavity and leading to the loss of the supporting periodontal tissues. This disease is generally chronic in nature and can persist in the absent of treatment. The bacterial etiology of chronic periodontal disease is complex, with a variety of organisms responsible for the initiation and progression of disease. Although over 400 different bacterial species have been detected in the oral cavity, only a limited number have been implicated as periodontal pathogens. Many of these organisms may also be present in periodontally healthy individuals and can exist in communal harmony with the host . In terms of the composition of microorganisms, the oral cavity is one of the most sophisticated ecosystems of the human organism. Saliva, gingival fluid, periodontal pocket, biofilm, and a number of other habitats contain approximately 700 different types of microorganisms. Dental plaque is a yellowish biofilm that builds up on the teeth. Biofilms contain communities of disease-causing bacteria and their uncontrolled accumulation has been associated with cavities and gum disease (both gingivitis and periodontitis). In the past, scientist studied bacteria by looking through a microscope at cells suspended in a water droplet. Today, scientists believe that the disease-causing bacteria do not exist as isolated cells, such as in the water droplet, but rather they adhere to various wetted surfaces in organized colonies that form diverse communities–biofilms. The aim of this presentation is to introduce recent advances in the biofilm of the periodontal disease generally and chronic periodontitis particularly